Outcomes of TIPS for Treatment of Gastroesophageal Variceal Hemorrhage - Parvinian, Ahmad; Gaba, Ron C. (Seminars in Interventional Radiology, 2014)
Variceal hemorrhage is a life-threatening complication of cirrhosis that requires a multidisciplinary approach to management. The transjugular intrahepatic portosystemic shunt (TIPS) procedure is a minimally invasive image-guided intervention used for secondary prevention of bleeding and as salvage therapy in acute hemorrhage. This review focuses on the role of TIPS in the setting of variceal hemorrhage, with emphasis on the pathophysiology and conventional management of variceal hemorrhage, current and emerging indications for TIPS creation, TIPS clinical outcomes, and the role of adjuvant embolotherapy.
Keywords: transjugular intrahepatic portosystemic shunt; gastroesophageal varices; hemorrhage; embolotherapy; interventional radiology